Tolerância e acúmulo de chumbo em acessos de Brassica juncea L - Bassegio, Chaiane (2020)
Identifying accessions of Brassica junceaL. capable of tolerating and accumulating lead (Pb) in the shoots is an important alternative for phytoremediation of contaminated soils. The objective of this work was to evaluate the tolerance and accumulation of B. junceaaccessions in Pb contaminated soil. The experiment was conducted in a 3 × 4 factorial scheme with three B. junceaaccessions (PI 180266, PI 649105 and PI 432379) and four levels of Pb (0, 90, 180 and 540 mg kg–1), with four repetitions. In addition to growth and accumulation of Pb in the shoot and roots, the transfer coefficient, translocation factor and tolerance index were calculated. Plant growth was reduced when soil Pb concentration increased to 540 mg kg–1. Pb concentrations in shoots and roots increased as soil concentration increased, reaching 80 mg kg–1in shoots and 900 mg kg–1in roots when plants were cultivated with contamination levels of 540 mg kg–1. The accessions of B. junceadiffered in the degree of Pb accumulation in the roots and shoot. The concentration of Pb in shoots in accession PI 180266 was 51% higher compared to accessions PI 649105 and PI 432379 when soil Pb concentration increased to 540 mg kg–1. The results indicated that there was genotypic difference, and B. juncea(AccPI 180266) is higher. tolerant to soil contaminated with Pb.